Perbandingan Rendemen dan Karakteristik Ekstrak Etanol 70% Daun Uncaria guianensis Berdasarkan Berbagai Metode Ekstraksi - Rahmawati, Noveri; Amelya Zenidah; Irfan, Nawwar (LPPM, Universitas Muhammadiyah Riau, 2025)
Uncaria guianensis is a medicinal plant from the Rubiaceae family, known for its wide range of pharmacological activities, particularly as an anti-inflammatory and immunomodulator. The leaves are rich in secondary metabolites such as alkaloids, flavonoids, tannins, and triterpenoids, whose potential is strongly influenced by the extraction method employed. This study aimed to compare the yield and characteristics of 70% ethanol extracts of Uncaria guianensis leaves obtained through four extraction methods: maceration, percolation, soxhlet extraction, and sonication. Leaf samples were collected from Kampar Regency, Riau, processed into powdered simplicia, and extracted using 70% ethanol. The results of the study showed that the soxhletation method produced the highest yield, namely 65.16%, followed by the maceration, percolation, and sonication methods with yields of 46.42%; 38.20%; and 35.82%, respectively. Phytochemical screening confirmed that all extracts tested positive for the presence of flavonoids, alkaloids, tannins, saponins, steroids, and triterpenoids. In terms of physicochemical characteristics, the soxhlet extract exhibited the best quality, with the lowest ash content (1.00%) and moisture loss (0.53%). In conclusion, soxhlet extraction is the most effective method for producing 70% ethanol extracts of Uncaria guianensis leaves, both in terms of quantity (yield) and quality (ash content and moisture loss).